2013
DOI: 10.1128/iai.00180-13
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Humoral and Cellular Responses to Multiple Sporozoite and Liver-Stage Malaria Antigens Using Exogenous Plasmid DNA

Abstract: A vaccine candidate that elicits humoral and cellular responses to multiple sporozoite and liver-stage antigens may be able to confer protection against Plasmodium falciparum malaria; however, a technology for formulating and delivering such a vaccine has remained elusive. Here, we report the preclinical assessment of an optimized DNA vaccine approach that targets four P. falciparum antigens: circumsporozoite protein (CSP), liver stage antigen 1 (LSA1), thrombospondin-related anonymous protein (TRAP), and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 59 publications
1
30
0
1
Order By: Relevance
“…Even though Plassmeyer et al [41] have demonstrated that >60% sporozoite inhibition can be achieved using PfCSP_TSR-specific monoclonal antibodies, our results indicate that CCT needs to be improved either by using a larger portion of either PfTRAP or PfCSP to introduce additional B-cell and/or T-cell epitopes, or by optimizing the immunization procedure by different dose regimens, adjuvants and formulations, as well as the choice of mouse strain [42]. Reduction of the apparent immuno dominance of the PfCSP_TSR, an observation that has also been made by Ferraro et al [43] after DNAvaccination using PfCSP, PfTRAP, PfCelTOS, and PfLSA1, could be a strategy to induce a more balanced immune response against the three antigens to improve the efficacy of this vaccine candidate.…”
Section: Biotechnology Journalsupporting
confidence: 75%
“…Even though Plassmeyer et al [41] have demonstrated that >60% sporozoite inhibition can be achieved using PfCSP_TSR-specific monoclonal antibodies, our results indicate that CCT needs to be improved either by using a larger portion of either PfTRAP or PfCSP to introduce additional B-cell and/or T-cell epitopes, or by optimizing the immunization procedure by different dose regimens, adjuvants and formulations, as well as the choice of mouse strain [42]. Reduction of the apparent immuno dominance of the PfCSP_TSR, an observation that has also been made by Ferraro et al [43] after DNAvaccination using PfCSP, PfTRAP, PfCelTOS, and PfLSA1, could be a strategy to induce a more balanced immune response against the three antigens to improve the efficacy of this vaccine candidate.…”
Section: Biotechnology Journalsupporting
confidence: 75%
“…Individuals living in malaria endemic regions mount IFN-γ responses to CelTOS suggesting that CelTOS is a target of protective immunity (Anum et al, 2015). CelTOS is also unique as it is a promising multi-stage malaria vaccine target (Bergmann-Leitner et al, 2010; Ferraro et al, 2013; Bergmann-Leitner et al, 2011, 2013) for both infection-blocking and transmission-blocking vaccines currently in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CelTOS has been identified as a promising malaria vaccine candidate referred to as Antigen 2 (Doolan et al, 2003). Immunization of mice with recombinant CelTOS results in humoral and cellular immune responses that reduced infection, demonstrating that targeting CelTOS is a viable approach for developing a malaria vaccine (Bergmann-Leitner et al, 2010; Ferraro et al, 2013; Bergmann-Leitner et al, 2011, 2013). Even though CelTOS is critical during cell traversal by malaria parasites and is a leading transmission- and infection-blocking malaria vaccine candidate, its function remains unknown as it has no sequence similarity to proteins of known function.…”
Section: Introductionmentioning
confidence: 99%
“…berghei sporozoite challenge (18). In addition, a DNA vaccine coding for Pf CelTOS has been shown to induce humoral and cellular responses against the protein in mice and nonhuman primates (19). …”
Section: Introductionmentioning
confidence: 99%